THE EFFECT OF PLATELET-RICH PLASMA ADMINISTRATION ON PROLIFERATION AND DIFFERENTIATION OF ENDOTHELIAL PROGENITOR CELLS IN PATIENTS WITH STABLE CORONARY HEART DISEASE - Hehanusa, Ronald Rendy (Stem Cell Research and Development Center, Universitas Airlangga, 2023)
Endothelial Progenitor Cells (EPCs) are crucial precursors to endothelial cells, playing a key role in regulating blood vessel structure and maintaining homeostasis to protect against inflammation and thrombosis, contributing to stable coronary heart disease (CHD). Growth factors stimulate signal transduction during EPC proliferation and differentiation. Platelet-Rich Plasma (PRP) contains widely recognized growth factors in angiogenesis. Our research aimed to analyze PRP's effects on EPC proliferation and differentiation in stable CHD patients. Using an experimental post-test control group design, mononuclear cells (MNCs) from peripheral blood were cultured with M-199 medium, divided into PRP, Platelet Poor Plasma (PPP), and control groups, and incubated for 14 days. EPC proliferation was quantified with CD34 markers using ANOVA. After 7 days, differentiated cells were counted with von Willebrand Factor (vWF) markers using the Mann-Whitney U test.EPC proliferation significantly increased in the PRP group (1.052 ± 0.16) compared to PPP (0.762 ± 0.19) and the control (0.068 ± 0.05, p=0.000). However, EPC differentiation showed no significant increase in the PRP group compared to PPP (0.00-0.30 vs. 0.00-0.20, p = 0.565) or the control (0.00-0.30 vs. 0.00-0.00, p = 0.064). Additionally, no significant increase in EPC differentiation was observed in the PPP group compared to the control (0.00-0.20 vs. 0.00-0.00, p = 0.144). PRP significantly enhanced EPC proliferation but did not significantly enhance differentiation in the peripheral blood of stable CHD patients compared to PPP and control groups.